Internal and External Factors Eï¬€ects towards Return on Assets in Indonesian Foreign Exchange Sharia Bank - Rizal, Rizal; Marlion, Farid Ahmad; Pasrizal, Himyar; Anita, Rini (IAIN Salatiga, 2021)
This study aims to analyze the inï¬‚uence of internal factors such as ï¬nancing and third-partyÂ funds, as well as external factors including inï¬‚ation, BI, and exchange rate against Return OnÂ Asset (ROA) at Indonesian Foreign Exchange Sharia Bank. Furthermore, the library researchÂ was used and quantitatively described. Also, using the total sampling technique, the researchÂ team obtained six sample banks, namely Bank Mega Syariah, Muamalat Indonesia, PaninÂ Dubai Syariah, BNI Syariah, BRI Syariah, and Bank Syariah Mandiri. The data includeÂ Balance Sheet and Proï¬t, Loss Financial Statements, as well as the published reports onÂ inï¬‚ation, BI, or exchange rates obtained in a quarterly period from 2015 to 2019. According toÂ the F-test, there was a signiï¬cant inï¬‚uence between the independent variables (Financing,Â Third Party Funds, Inï¬‚ation, BI, and Exchange Rates) on the dependent (ROA). Meanwhile,Â the t-test showed there was no signiï¬cant eï¬€ect of partial financing, Third Party Funds, BI rateÂ (X ), and Kurs (X ) on the ROA. Therefore, this study showed there was an increase in ROAÂ because the society involves in ï¬nancing due to high inï¬‚ation.